DIMAS (Diabetes Management Support) Application: Mobile-Phone Based Intervention to Support Diabetes Self-Management Activities - Annisa Wuri Kartika; Widyatuti Widyatuti; Etty Rekawati (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The self-management process in Diabetes Mellitus (DM) is essential to improve glycemic control. Currently, COVID-19 leading to a significant limitation in services and accessibility, especially regular support for diabetes patients. The utilization of DIMAS Mobile App is expected to be a support system to overcome these problems. This application has three menus such as health education containing information about diabetes, nutrition, medication, exercise, stress management, and foot care; self-care monitoring containing medication reminders, blood sugar and exercise records; and consultation with nurses. This study aimed to determine the effect of DIMAS (Diabetes Management Support) application on Diabetes Self-Management activities. Methods: Using an experimental study with One Group Pre-Posttest Design, the self-management activities were measured among 24 respondents after four weeks of intervention. The intervention was carried out with the DIMAS app and WhatsApp communication. Using the Summary of Diabetes Self-Care Activity (SDSCA) questionnaire, the data were analysed with one paired sample t-test using SPSS 22. Results: Statistically significant changes were observed between pre and post-intervention measures: DSM activities with SDSCA (p=0,000) and the level of knowledge (p=0,000). The results showed that the biggest change in self-care activity was foot care and exercise with the increase of scoring was 2.4 and 0.8 respectively. Respondents stated that the application was useful for reminding them to take medication and communicating with nurses. Conclusion: The application makes it easier for patients to keep connected with nurses despite being constrained by distance and provides practical benefits in nursing services at home. REFERENCE 1. Kemenkes RI. 2020. Infodatin-2020-Diabetes Melitus.pdf. 2. Jing X, Chen J, Dong Y, Han D, Zhao H, Wang X, Gao F, Li C, Cui Z, Liu Y, Ma J. (2018). Related factors of quality of life of type 2 diabetes patients: a systematic review and meta-analysis. Health Qual Life Outcomes. 2018 Sep 19;16(1):189. doi: 10.1186/s12955-018-1021-9. 3. Sayeed, K. A., Qayyum, A., Jamshed, F., Gill, U., Usama, S. M., Asghar, K., & Tahir, A. (2020). Impact of Diabetes-related Self-management on Glycemic Control in Type II Diabetes Mellitus. Cureus, 12(4), e7845. doi:10.7759/cureus.7845. 4. Trevisan DD, São-João T, Cornélio M, Jannuzzi F, de Sousa MR, Rodrigues R, Lima MH. (2019). Effect of an ‘implementation intention’ intervention on adherence to oral anti-diabetic medication in Brazilians with type 2 diabetes. Patient Educ Couns. 2020 Mar;103(3):582-588. doi: 10.1016/j.pec.2019.10.003. 5. Amer FA, Mohamed MS. (2018). Influence of self-efficacy management on adherence to self-care activities and treatment outcome among diabetes mellitus type 2 Sudanese patients. Pharm Pract (Granada). 2018;16(4):1274. doi: 10.18549/PharmPract.2018.04.1274. 6. Hurst CP, Rakkapao N, Hay K. (2020). Impact of diabetes self-management, diabetes management self-efficacy and diabetes knowledge on glycemic control in people with Type 2 Diabetes (T2D): A multicenter study in Thailand. PLoS One. 2020;15(12 December):1–14. doi: 10.1371/journal.pone.0244692 7. McBrien KA, Naugler C, Ivers N, Weaver RG, Campbell D, Desveaux L, Hemmelgarn BR, Edwards AL, Saad N, Nicholas D, Manns BJ. (2017). Barriers to care in patients with diabetes and poor glycemic control-A cross-sectional survey. PLoS One. 2017;12(5):e0176135. doi: 10.1371/journal.pone.0176135. 8. Robat Sarpooshi D, Taghipour A, Mahdizadeh M, Peyman N. Enablers of and Barriers to Effective Diabetes Self-Care in Iran: A Qualitative Study. Patient Relat Outcome Meas. 2020;11:109-118. doi: 10.2147/PROM.S241170. 9. Meiqari L, Al-Oudat T, Essink D, Scheele F, Wright P. How have researchers defined and used the concept of “continuity of care” for chronic conditions in the context of resource-constrained settings? A scoping review of existing literature and a proposed conceptual framework. Heal Res Policy Syst. 2019;17(1):1–14. doi: 10.1186/s12961-019-0426-1. 10. WHO WHO. COVID-19 significantly impacts health services for noncommunicable diseases. Https://WwwWhoInt/News-Room/Detail/01-06-2020-Covid-19-Significantly-Impacts-Health-Services-for-Noncommunicable-Diseases [Internet]. 2020;41(June):1–3. Available from: https://www.who.int/news-room/detail/01-06-2020-covid-19-significantly-impacts-health-services-for-noncommunicable-diseases 11. Ruissen MM, Regeer H, Landstra CP, Schroijen M, Jazet I, Nijhoff MF, et al. Increased stress, weight gain and less exercise in relation to glycemic control in people with type 1 and type 2 diabetes during the COVID-19 pandemic. BMJ Open Diabetes Res Care. 2021;9(1):1–7. doi: 10.1136/bmjdrc-2020-002035. 12. Sauchelli S, Bradley J, England C, Searle A, Whitmarsh A. Exploring support needs of people living with diabetes during the coronavirus COVID-19 pandemic: Insights from a UK survey. BMJ Open Diabetes Res Care. 2021;9(1):1–11. doi: 10.1136/bmjdrc-2021-002162. 13. Sarría-Santamera A, Yeskendir A, Maulenkul T, Orazumbekova B, Gaipov A, Imaz-Iglesia I, et al. Population health and health services: Old challenges and new realities in the COVID-19 era. Int J Environ Res Public Health. 2021;18(4):1–5. doi: 10.3390/ijerph18041658. 14. Knox ECL, Quirk H, Glazebrook C, Randell T, Blake H. Impact of technology-based interventions for children and young people with type 1 diabetes on key diabetes self-management behaviours and prerequisites: A systematic review. BMC Endocr Disord. 2019;19(1):1–14. doi: 10.1186/s12902-018-0331-6. 15. Long H, Bartlett YK, Farmer AJ, French DP. Identifying brief message content for interventions delivered via mobile devices to improve medication adherence in people with type 2 diabetes mellitus: A rapid systematic review. J Med Internet Res. 2019;21(1):1–20. doi: 10.2196/10421. 16. Alanzi T. mHealth for diabetes self-management in the kingdom of Saudi Arabia: Barriers and solutions. J Multidiscip Healthc. 2018;11:535–46. doi: 10.2147/JMDH.S174198. 17. Bene BA, O’Connor S, Mastellos N, Majeed A, Fadahunsi KP, O’Donoghue J. Impact of mobile health applications on self-management in patients with type 2 diabetes mellitus: Protocol of a systematic review. BMJ Open. 2019;9(6). doi: 10.1136/bmjopen-2018-025714. 18. Sampa MB, Hoque MR, Islam R, Nishikitani M, Nakashima N, Yokota F, et al. Redesigning portable health clinic platform as a remote healthcare system to tackle COVID-19 pandemic situation in unreached communities. Int J Environ Res Public Health. 2020;17(13):1–14. doi: 10.3390/ijerph17134709. 19. Cui M, Wu X, Mao J, Wang X, Nie M. T2DM self-management via smartphone applications: A systematic review and meta-analysis. PLoS One [Internet]. 2016;11(11):1–16. doi:10.1371/journal.pone.0166718 20. Riegel B, Jaarsma T, Lee CS, Strömberg A. Integrating symptoms into the middle-range theory of self-care of chronic illness. Adv Nurs Sci. 2019;42(3):206–215. doi: 10.1097/ANS.0000000000000237. 21. Abdulrahman M, Husain ZSM, Abdouli KA, Kazim MN, Sayed Mahdi Ahmad F, Carrick FR. Association between knowledge, awareness, and practice of patients with type 2 diabetes with socio-economic status, adherence to medication and disease complications. Diabetes Res Clin Pract [Internet]. 2020;163(April):108124. doi:10.1016/j.diabres.2020.108124 22. Zioga E, Kazakos K, Dimopoulos E, Koutras C, Marmara K, Marmara E, et al. Adherence and Quality of Life in Patients With Type II Diabetes Mellitus in Northern Greece. Mater Socio Medica. 2016;28(4):258. doi: 10.5455/msm.2016.28.258-262. 23. Kadariya S, Aro AR. Barriers and facilitators to physical activity among urban residents with diabetes in Nepal. PLoS One. 2018;13(6):1–21. doi: 10.1371/journal.pone.0199329. 24. Egan AM, Mahmood WAW, Fenton R, Redziniak N, Kyaw Tun T, Sreenan S, et al. Barriers to exercise in obese patients with type 2 diabetes. Qjm. 2013;106(7):635–8. doi: 10.1093/qjmed/hct075 25. Wagner H, Fischer H, Degerblad M, Alvarsson M, Gustafsson T. Improvement of insulin sensitivity in response to exercise training in type 2 diabetes mellitus is associated with vascular endothelial growth factor A expression. Diabetes Vasc Dis Res. 2016;13(5):361–6. doi: 10.1177/1479164116651391 26. Soelistijo S, Novida H, Rudijanto A, Soewondo P, Suastika K, Manaf A, et al. Konsesus Pengelolaan Dan Pencegahan Diabetes Melitus Tipe2 Di Indonesia 2015. Perkeni. 2015. 82 p. 27. Farah BQ, do Prado WL, Malik N, Lofrano-Prado MC, de Melo PH, Botero JP, et al. Barriers to physical activity during the COVID-19 pandemic in adults: a cross-sectional study. Sport Sci Health [Internet]. 2021;17(2):441–7. doi:10.1007/s11332-020-00724-5 28. Miikkola M, Lantta T, Suhonen R, Stolt M. Challenges of foot self-care in older people: A qualitative focus-group study. J Foot Ankle Res. 2019;12(1):1–10. doi: 10.1186/s13047-019-0315-4 29. Sari Y, Upoyo AS, Isworo A, Taufik A, Sumeru A, Anandari D, et al. Foot self-care behavior and its predictors in diabetic patients in Indonesia. BMC Res Notes [Internet]. 2020;13(1):1–7. doi:10.1186/s13104-020-4903-y 30. Adu, M. D., Malabu, U. H., Malau-Aduli, A., & Malau-Aduli, B. S. (2019). Enablers and barriers to effective diabetes self-management: A multi-national investigation. PloS one, 14(6), e0217771. doi:10.1371/journal.pone.0217771. 31. Goh G, Tan NC, Malhotra R, Padmanabhan U, Barbier S, Allen JC, et al. Short-term trajectories of use of a caloric-monitoring mobile phone app among patients with type 2 diabetes mellitus in a primary care setting. J Med Internet Res. 2015;17(2). doi: 10.2196/jmir.3938.